(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Traditional healers possess a rich knowledge on the use of medicinal plants for the treatment of various diseases. Enicostemma axillare (Lam). Raynal is one plant, used by healer to treat gastric cancer or ulceration. We assessed the phytochemical components of leaf extract for its antibacterial activity, to add value and provide an evidence-base for their traditional use. The antibacterial potential of the leaf extract was tested against Helicobacter pylori using agar well diffusion method. The minimum inhibitory concentration (MIC) of ethanol extract exhibited the (MIC) against H. pylori ranged from 200µg/ml - 250µg/ml followed by chloroform extract. Gas chromatography and mass spectrum (GC-MS) analysis confirms the occurrence of different components in the ethanol and chloroform leaf extract of the studied species.